1990
DOI: 10.1016/0163-7258(90)90094-i
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and action of amino acid analog anti-cancer agents

Abstract: Abstract--The preclinical pharmacology, antitumor activity and toxicity of seven of the more important amino acid analogs, with antineoplastic activity, is discussed in this review. Three of these compounds are antagonists of L-glutamine: acivicin, DON and azaserine; and two are analogs of L-aspartic acid: PALA and L-alanosine. All five of these antimetabolites interrupt cellular nucleotide synthesis and thereby halt the formation of DNA and/or RNA in the tumor cell. The remaining two compounds, buthionine sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
177
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(181 citation statements)
references
References 177 publications
3
177
0
1
Order By: Relevance
“…The rest of our work is focused on the use of two irreversible glutamine analog CTP synthetase inhibitors, 6-diazo-5-oxo-L-norleucine (DON) and ␣-amino-3-chloro-4,5-dihydro-5-isoxazoleacetic acid (acivicin). These drugs have been used extensively in clinical trials against various cancers, and at least acivicin is known to penetrate the blood-brain barrier (6). We found that both drugs inhibited the proliferation of cultured trypanosomes at much lower concentrations than the levels measured in the blood of cancer patients.…”
mentioning
confidence: 75%
“…The rest of our work is focused on the use of two irreversible glutamine analog CTP synthetase inhibitors, 6-diazo-5-oxo-L-norleucine (DON) and ␣-amino-3-chloro-4,5-dihydro-5-isoxazoleacetic acid (acivicin). These drugs have been used extensively in clinical trials against various cancers, and at least acivicin is known to penetrate the blood-brain barrier (6). We found that both drugs inhibited the proliferation of cultured trypanosomes at much lower concentrations than the levels measured in the blood of cancer patients.…”
mentioning
confidence: 75%
“…Acivicin, 6-diazo-5-oxo-L-norleucine, and azaserine, three of the most widely studied analogs (Figure 1), all demonstrated variable degrees of gastrointestinal toxicity, myelosuppression, and neurotoxicity (72). Because these agents non-selectively target glutamine-consuming processes, recent interest has focused on developing methods directed at specific nodes of glutamine metabolism.…”
Section: Pharmacological Strategies To Inhibit Glutamine Metabolism Imentioning
confidence: 99%
“…Thus deamidation is a control point for glutamine metabolism in tumor cells. In xenografts, glutaminase expression is temporally correlated with maximal growth rate, and suppression of glutaminase activity limits tumor growth [55][56][57].…”
Section: How Does Glutamine Metabolism Support Biosynthetic Activitiementioning
confidence: 99%